PENERAPAN PRAKTIK MSDM DAN IMPLIKASINYA PADA KINERJA UKM - Rahab, Rahab (Fokus Ekonomi, 2006)
The increasing business competition strives small medium enterprises (SMEs) to improve human competency in gaining competitive advantages. The aim of this paper explains relationship between contextual dimension and structural dimension that influence implementation of human resources management (HRM) practice and SMEs‘s performance. Implementation of HRM practice is one of  SMEs’s way to improve their human resource aspect and it have differences characteristics with large firms. Implementation HRM practice in SMEs still have many  barriers that caused by limited resources (time and financial), lack of management skill, lack of understanding benefit of HRM practices to increasing firm’s performance. Keyword:  Small Medium Enterprises (SMEs), Human resources management (HRM), firm’s performance